The Impact of Academic Support, Parental Support, and Peer Support on the Entrepreneurial Interest of Students with Special Needs at SLB Negeri Semarang - Lusia Ira Agustina; Ahmad Sehabuddin (Economic Education Analysis Journal, 2026)
This study investigates how academic support, parental support, and peer support influence entrepreneurial interest among students with special needs at the senior secondary special education level (SMALB) in Indonesia. Grounded in Ecological Systems Theory, the study addresses a notable gap in entrepreneurship research, which has largely overlooked the entrepreneurial development of students with special needs, particularly within supportive social and educational ecosystems. A quantitative approach was employed using a population of 136 students and a sample of 101 respondents. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression. The findings reveal that academic support has a significant positive effect on entrepreneurial interest (10.43%), followed by parental support (5.29%), while peer support shows no significant influence. These results highlight the central role of proximal institutional and family environments in fostering entrepreneurial orientation among students with special needs, whereas peer interaction appears less directly connected to entrepreneurial motivation in this context. The study contributes to the entrepreneurship and special education literature by emphasizing the ecological nature of entrepreneurial interest formation and the importance of inclusive educational and family-based empowerment strategies to support entrepreneurial pathways for students with special needs.